2005
DOI: 10.1590/s1519-69842005000100015
|View full text |Cite
|
Sign up to set email alerts
|

Cladocerans (Branchiopoda) of a tropical estuary in Brazil

Abstract: The study was conducted in the Capibaribe river estuary in Recife (Brazil) to assess the role played by cladocerans in a eutrophic environment. Samplings were carried out monthly at 4 fixed stations along the estuary from July 1987 to June 1988. Collections were made with a plankton net of 65 micrometers mesh size. Six cladocerans species were registered: Penilia avirostris, Diaphanosoma spinulosum, Chlydorus barroisi, Ceriodaphnia rigaudi, Ilyocryptus spinifer, and Moina micrura. The most frequent species was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
10
0
3
Order By: Relevance
“…Já D. colombiensis, observada no Açude de Apipucos (Recife), é uma espécie que conta com apenas um registro de ocorrência no país, no estado do Rio de Janeiro (Lopes et al 2006). Além da inclusão de novas espécies, feita por este estudo e por diversos autores (Crispim & Watanabe 2000, Paranaguá et al 2005, Elmoor-Loureiro et al, 2009), a presente lista (Tabela 2) apresenta algumas diferenças em relação à previamente disponível para o estado de Pernambuco (Elmoor-Loureiro 2000). Em grande parte, trata-se de alterações taxonômicas posteriores, como é o caso de: Alona ossiani Sinev, 1998, membro neotropical do complexo Alona affinis (Sinev 1998);Anthalona verrucosa (Sars, 1901), antes citada nos gêneros Biapertura e Alona (Van Damme et al 2011); Alonella dadayi Birge, 1910, transferida do gênero Disparalona (cf.…”
Section: Discussionunclassified
“…Já D. colombiensis, observada no Açude de Apipucos (Recife), é uma espécie que conta com apenas um registro de ocorrência no país, no estado do Rio de Janeiro (Lopes et al 2006). Além da inclusão de novas espécies, feita por este estudo e por diversos autores (Crispim & Watanabe 2000, Paranaguá et al 2005, Elmoor-Loureiro et al, 2009), a presente lista (Tabela 2) apresenta algumas diferenças em relação à previamente disponível para o estado de Pernambuco (Elmoor-Loureiro 2000). Em grande parte, trata-se de alterações taxonômicas posteriores, como é o caso de: Alona ossiani Sinev, 1998, membro neotropical do complexo Alona affinis (Sinev 1998);Anthalona verrucosa (Sars, 1901), antes citada nos gêneros Biapertura e Alona (Van Damme et al 2011); Alonella dadayi Birge, 1910, transferida do gênero Disparalona (cf.…”
Section: Discussionunclassified
“…Among the cladocerans, Bosminia longirostis (3440 ind m Tropical and temperate limnological comparative studies indicated that whereas oligotrophic habitats are dominated by copepods, more eutrophic habitats are dominated by rotifers and cladocerans. The dominance of small rotifers and cladocerans in eutrophic ecosystems is thought to be directly associated with their ability to effectively avoid typically abundant cyanobacteria and feed on smaller algal particles (Paranaguá et al, 2005). These conditions could be related to the higher abundance of rotifers (comprising 81.89% of all samples) in the Karakaya Dam Lake, where small algae are abundant (Gokce and Ozhan, 2011).…”
Section: Nutrient Composition and Dynamicsmentioning
confidence: 99%
“…Because of this, they can play a crucial role in the secondary production in coastal and estuarine waters (Modigh et al, 1996;Lipej et al, 1997;Marazzo & Valentin, 2000, 2001. They are also sensitive to disturbance, like eutrophication due to anthropogenic impacts such as heavy urbanization, domestic and industrial pollutants, and sewage disposal (Wong et al, 1992;Siokou-Frangou et al, 1998;Kamburska et al, 2003;Valentin & Marazzo, 2003;Paranaguá et al, 2005;Shiganova, 2005).…”
Section: Introductionmentioning
confidence: 99%